The reason we drink alcohol is rooted in our evolution - Carrigan, Matthew A. (2016)
We have resurrected ancient enzymes from our primate ancestors and identified several mutations occurring approximately 10 million years ago that endowed our ancestors with an enhanced capacity to metabolize ethanol.  This episode of enzyme evolution coincided with a global climate change associated with shrinking African forests and our ancestor’s transition from an arboreal lifestyle to a terrestrial lifestyle where highly fermented fruit is more common. These studies suggest that the evolution of our ancestor’s enzymes may have enabled our ancestors to exploit an alternative source of nourishment during a time when food was scarce.